Measuring the Flow Functions of Pharmaceutical Powders Using the Brookfield Powder Flow Tester and Freeman FT4 - Mark Christopher Leaper (MDPI AG, 2021)
This study examined the feasibility of combining data from different powder flow testers to determine the flow function characteristics of pharmaceutical powders. The Brookfield PFT and Freeman FT4 can measure flow function over different scales of consolidation load but were found to be most complementary with CRM limestone powder and lactose. The brittle behaviour of Easytab particles at higher loads made obtaining repeatable results with the FT4 challenging. By using the method of Wang et al., where the flow function coefficient ffc is plotted against the dimensionless cohesion C* (measured cohesion Ta divided by the initial compaction I), a plot was formed which could be used to predict the behaviour of other systems, which compared well with previous studies.